Laboratory attitudes and practices in the conservation of biological tissues for research purposes in Cote d’Ivoire - Kintossou, Ambroise Kouamé; N'Dri, Mathias Kouamé; Money, Marcelle; Diané, Maxime Kouao; Cissé, Souleymane; Soumahoro, Man Koumba; Coulibaly, Amadou Founzégué; Djaman, Joseph Allico; Dosso, Mireille (Open Science Journal, 2020)
Background : Since 2009, Côte d'Ivoire has had a biobank, which now houses the ECOWAS regional biobank. This biobank intends to set up a biological tissue bank for research. In Côte d'Ivoire, several public and private structures handle biological tissues. However, we do not know which ones are involved in the conservation of biological tissues and their related procedures. To ensure optimal conservation of biological tissues at the biobank of Côte d'Ivoire, it is necessary to conduct a study on the state of the art of tissue preservation in Côte d'Ivoire. The objective of our work is to know the attitudes and practices of biological tissue preservation in Côte d'Ivoire. Methods : This is a descriptive study carried out in biological analysis laboratories in the south of the Ivory Coast. Results : A total of 66 laboratories agreed to answer the questionnaire that was proposed to them. Among them, only 21.21% kept biological tissues, of which 42.86% were human tissues, 35.71% animal tissues and 21.43% plant tissues. Human tissuesz were stored in formalin at room temperature for a period ranging from 2 weeks to 6 months. Animal biopsies and surgical specimens were stored in formalin and at -80°C for an indefinite period of time. Plant tissues were stored at room temperature and +4°C for an indefinite period of time. Conclusion : The conservation quality of biological tissues still needs to be improved.